Plant invasion is associated with higher plant–soil nutrient concentrations in nutrient‐poor environments. (13th July 2016) - Sardans, Jordi; Bartrons, Mireia; Margalef, Olga; Gargallo‐Garriga, Albert; Janssens, Ivan A.; Ciais, Phillipe; Obersteiner, Michael; Sigurdsson, Bjarni D.; Chen, Han Y. H.; Peñuelas, Josep
Abstract: Plant invasion is an emerging driver of global change worldwide. We aimed to disentangle its impacts on plant–soil nutrient concentrations. We conducted a meta‐analysis of 215 peer‐reviewed articles and 1233 observations. Invasive plant species had globally higher N and P concentrations in photosynthetic tissues but not in foliar litter, in comparison with their native competitors. Invasive plants were also associated with higher soil C and N stocks and N, P, and K availabilities. The differences in N and P concentrations in photosynthetic tissues and in soil total C and N, soil N, P, and K availabilities between invasive and native species decreased when the environment was richer in nutrient resources. The results thus suggested higher nutrient resorption efficiencies in invasive than in native species in nutrient‐poor environments. There were differences in soil total N concentrations but not in total P concentrations, indicating that the differences associated to invasive plants were related with biological processes, not with geochemical processes. The results suggest that invasiveness is not only a driver of changes in ecosystem species composition but that it is also associated with significant changes in plant–soil elemental composition and stoichiometry.